Assessment of treatment outcomes in the management of club foot using the ponseti technique: A cross-sectional study - Joseph E Asuquo; Enembe O Okokon; Omolade Ayoola Lasebikan; Chukwuemeka Okechukwu Anisi; Best J Asuquo; Innocent Egbeji Abang; Akpet E Obaji; Kingsley C Chigbundu (Wolters Kluwer Medknow Publications, 2024)
Background: The Ponseti technique remains the preferred method for club foot treatment. Although measures of treatment outcomes have been well documented, there is no consensus on the determinants of those outcomes. This study aims to assess treatment outcomes and the factors which can influence treatment outcomes. Materials and Methods: This is a cross-sectional study. A total of 472 children representing 748 feet in total were recruited. Patient characteristics such as age at presentation, gender, tenotomy, walking with or without deformity, parental educational status and occupation were documented. Outcomes of care were assessed using indictors such as parents' satisfaction with the outcome of treatment and the patients' ambulation without deformity. The relationships between the determinant factors and these outcomes were explored using multivariable binary logistic regression. Results: Most of the children (69.1%) were aged below 2 years. Brace compliance was very high (89.9%). The pre-treatment average Pirani scores were 3.9 ± 1.8 and 4.3 ± 1.8 for the right and left feet, respectively. Majority (88.3%) of the children achieved ambulation without deformity, whereas most (87%) of the parents were satisfied with the treatment outcomes. In total, parental satisfaction with child's treatment outcomes was lower in parents who were not formally educated odds ratio (OR) = 0.19 (95% confidence interval [CI] 0.08-0.43), but parental satisfaction was lower if the child had higher Pirani score OR = 0.77 (95% CI 0.62-0.96). Children who had more casts applied to the affected foot were more likely to walk without deformity OR = 1.24 (95% CI 1.01-1.52). Conclusions: This study revealed that treatment outcomes in children with club foot can be determined by some sociodemographic and treatment-related factors.